2002
DOI: 10.4269/ajtmh.2002.66.317
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C among child transfusion and adult renal dialysis patients in Indonesia.

Abstract: Abstract. Hepatitis C virus (HCV) prevalence among high-risk pediatric and adult patients was evaluated. The study included 269 adults and 150 children in a case-control research design. Risk factors of HCV exposure in Indonesia were assessed among adult renal dialysis patients and pediatric patients who received multiple blood transfusions. A high prevalence of anti-HCV was found among the adult renal dialysis patients, measured by second-generation electroimmunoassay tests. Family members of dialysis patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Although blood transfusion has been pointed out as an important risk factor for viral hepatitis within hemodialysis population (Covic et al 1999, Chanpong et al 2002, Hinrichsen et al 2002, in the present investigation this factor was not associated with HBV and HCV infections. Therefore, probably the screening of blood products for HBsAg, anti-HBc and anti-HCV in Brazilian blood banks, and the use of erythropoietin for anemia treatment should have contributed to reduce this risk among our hemodialysis patients.…”
Section: Discussionsupporting
confidence: 41%
See 1 more Smart Citation
“…Although blood transfusion has been pointed out as an important risk factor for viral hepatitis within hemodialysis population (Covic et al 1999, Chanpong et al 2002, Hinrichsen et al 2002, in the present investigation this factor was not associated with HBV and HCV infections. Therefore, probably the screening of blood products for HBsAg, anti-HBc and anti-HCV in Brazilian blood banks, and the use of erythropoietin for anemia treatment should have contributed to reduce this risk among our hemodialysis patients.…”
Section: Discussionsupporting
confidence: 41%
“…Recent data from Indonesia, Syria, and Jordan revealed rates of 63.4%, 48.9% and 34.6%, respectively (Othman & Monem 2001, Bdour 2002, Chanpong et al 2002. In Brazil, anti-HCV prevalence ranges from 20.3% to 64.7% (Vanderborght et al 1995, Carneiro et al 2001, Santana et al 2001, Busek et al 2002.…”
Section: Discussionmentioning
confidence: 99%
“…However, the prevalence was lower than that in children with hematological diseases (39%) [41] and in hemophilia patients (56.9%) [42]. The anti-HCV antibody-positive rate was significantly higher among the IDUs; however, 28.8% of the anti-HCV antibody-positive samples were derived from the nonIDUs.…”
Section: Discussionmentioning
confidence: 66%
“…[13][14] Patient's age and the number of transfused blood products are the 2 factors most consistently associated with increased prevalence of HBV and HCV infection in dialysis patients, irrespective of geographic location. 16 In this study the prevalence of HBV and HCV was significantly higher in patients those who received more than 5 blood transfusions than those who received less than 5 blood transfusions. Chanpong et al, and Hinrichson et al, noted that higher rate of seropositivity is found in patients with multiple transfusions.…”
Section: Discussionmentioning
confidence: 51%
“…Chanpong et al, and Hinrichson et al, noted that higher rate of seropositivity is found in patients with multiple transfusions. [16][17] As these viral infections have common modes of transmission, presence of co-infection in patients is not rare and is relatively high in transfusion recipients. The prevalence of dual infection of HCV and HBV ranges from 3-3.7% in India.…”
Section: Discussionmentioning
confidence: 99%